THE ANTECEDENT AND CONSEQUENCES OF CUSTOMER TRUST - Novita Dian Sari; Asep Hermawan (Universitas Trisakti, 2019)
Purpose - The purpose of this research was analyzed the effect of Competence on Customer Trust, was analyzed the effect of Stability on Customer Trust; and was analyzed the effect of Integrity on Customer Trust, was analyzed the effect of Customer Orientation on Customer Trust, was analyzed the effect of Transparancy on Customer Trust, was analyzed the effect of Customer Experience on Customer Trust, was analyzed the effect of Customer Trust on Customer Loyalty. Design/methodology/approach - The methodology of this research were collected from one hundred and seventy private banking consumer’s as respondent. Respondents were asked to answer a questionnaire about competence, stability, integrity, customer orientation, transparency, customer experience, customer trust, customer loyalty. Findings – Finding and contribution in this research was examined competence and transparency are the most important determinant of customer trust. Originality/Value - Research limitations/ implication in this research was indicated one hundred and seventy private banking consumer’s as respondent in this research. The data were collected from private banking consumer’s with purposive sampling.